Acanthotomicus suncei, a new sweetgum tree pest in China (Coleoptera: Curculionidae: Scolytinae: Ipini) - Gao, Lei; Cognato, Anthony I. (Zootaxa, 2018)
A new species of bark beetle, Acanthotomicus suncei Cognato, that kills sweetgum (Liquidambar spp.) is described. The new species is distinguished from the other Acanthotomicus species by the placement of elytral declivital spines on interstriae 2, 4, 6, 8 and the connection of spines 1 and 2 by a tumescence. Notes on the bark beetle’s potential damage to sweetgum are given.